AI and Personal Data Regulation: From Public Authority Enforcement to Civil Liability Law (TEST BioLaw Journal - Rivista di BioDiritto, 2026)
The administrative procedure before the supervisory authority and the possibility to act under liability law are remedies both available under AI act and GDPR. On one hand, the supervisory authority has an ambivalent role. It operates at the intersection of market regulation and the protection of fundamental rights, combining both ex-ante and ex-post powers. On the other hand, liability law must not be undervalued in ensuring the enforcement of these regulations, especially given its preventive (prophylactic) function. Analyzing these remedies allows to highlight how the GDPR will be a key component in ensuring the effectiveness of the AI Act. Conversely, it illustrates how artificial intelligence provides a new perspective on certain provisions of data protection law.
Keywords: personal data protection; artificial intelligence; regulation; civil liability; supervisory authorities